Effect of Balamula Ghrita Uttarabhaktika Sneha and Mashasaindhava Taila Pichu in the Management of Cervical Spondylosis - A Single Arm Prospective Open Randomized Clinical Study - S. Ranjani,; Pradeep Kumar Moharana,; S. Swaminathan, (AYUSHDHARA, 2022)
In Ayurveda prevalence of Vayu mahabhuta is considered as prime factor that causes deterioration of qualities of Kapha in Greeva stana hence prescription of drugs having Vatanuloma and qualities of Prithvi and Jala mahabhuta would be very effective. In the present study humble attempt is made to evaluate the effect of Balamula Ghritam internally and combined with Mashasaindhava Tailam as external pack in arresting further degeneration. Materials and methods: 40 patients fulfilling the inclusion criteria after signing the informed consent form were selected from SJSACH [IEC N0-IEC/SJSACH/ 05/2021, CTRI N0 - CTRI/2021/07/034968]. It is a single arm prospective open randomized clinical study. Patients were administered with 10ml of Balamula Ghritam morning and night after food and Mashasaindhava Tailam as pichu (external pack) over the cervical area for 21 days with two follow ups after the completion of the trial. Result: Subjective parameters were assessed using Friedman test and Wilcoxon signed rank test and objective parameters were assessed using paired sample t test. All the parameters had highly significant results with significant p value at the end of the treatment. Conclusion: The combined effect of Balamula Ghritam and Mashasaindhava Tailam was very effective in the management of cervical spondylosis. The critical analysis of the contents of Balamula Ghritam and Mashasaindhava Tailam acts as antioxidant, removes free radicals ROS, reduces the activity of osteoclast and bone resorption by inhibiting RANKL receptor pathway. It also has anti- inflammatory, anti-arthritic, anti-analgesic effect that found to be effective in reducing the symptoms of cervical spondylosis.